Mixed layer eddies supply nutrients to enhance the spring phytoplankton bloom - Simoes-Sousa, Iury T.; Tandon, Amit; Pereira, Filipe; Lazaneo, Caue Z.; Mahadevan, Amala (Frontiers in Marine Science, 2022)
Mixed layer eddies resulting from baroclinic instability of fronts convert horizontal buoyancy gradients into vertical stratification, shoaling the mixed layer. In light-limited regimes -- high-latitudes -- this process can initiate phytoplankton blooms prior to the springtime warming. The question is whether mixed layer eddies can enhance the spring bloom by delivering nutrients from beneath the mixed layer. We couple a submesoscale-resolving model (SUB) with a simple ecosystem model and examine the role of mixed layer eddies on the development of the spring bloom. We compare the SUB simulation to two coarser resolution (10km) simulations, one that includes a mixed layer eddy parameterization (MLE) and another that prescribes the restratification from SUB and advects the biogeochemical tracers using geostrophic velocities (NVF). The MLE simulates restratification of the mixed layer and bloom onset, but the spring bloom has a deficit of 10-13% in the new production compared to SUB. The NVF has the same restratification as SUB, and with no vertical flux of nutrients, leads to a spring bloom with a 32-40% new production deficit compared to SUB. Submesoscale processes lead to exchange across the mixed layer base, which is not represented in coarse resolution model simulations, even with mixed layer eddy parameterizations. Our results show that nutrients supplied by mixed layer eddies are important to enhance the spring bloom.